Incidence and severity of arrhythmias and conduction disturbance after repair of tetralogy of Fallot - Günal, Nazlıhan; Tokel, Kürşad; Kahramanyol, Öz; Özer, Sema; Çeliker, Alpay; Ekici, Enver; Yurdakul, Yurdakul; Kutsal, Ali (The Turkish Journal of Pediatrics, 1997)
Ventricular and supraventricular arrhythmias and conduction disturbances were evaluated by routine electrocardiography and 24-hour ambulatory monitoring in 31 patients who underwent correction of tetralogy of Fallot. The interval from operation to the study was 1 month to 14 years (mean 4.8 ± 2.8). Complete right bundle branch block occurred in 22 (71%) patients and incomplete right bundle branch block in 9 (29%) patients. Bifascicular block with right bundle branch block and left axis deviation (LAD) occurred in one patient. Two patients had second degree type II atrioventricular block. Twenty-four-hour ambulatory electrocardiographic monitoring was performed in all patients and they were divided in two groups according to the frequency of ventricular arrhythmias (Lown classification). Group 1 included the 23 patients who had no arrhythmia or rare ventricular arrhythmias (Lown grade 0-1). Group 2 was comprised of eight patients (26%) with significant ventricular arrhythmias (Lown grade 2-5). Twelve patients (39%) had supraventricular arrhythmias, three patients rare supraventricular tachycardia attacks, and seven patients occasional supraventricular ectopies. One patient had bradycardia-tachycardia attacks and one patient had junctional tachycardia. There was no correlation between age at the time of surgery and ventricular arrhythmias. Of the patients who had ventricular and supraventricular arrhythmias of various degrees on ambulatory monitoring, two had significant arrhythmias on routine electrocardiogram. Symptoms were rare in these patients. In conclusion, both supraventricular and ventricular arrhythmias were found in considerable frequency in our patients. As ventricular arrhythmias may be the cause of sudden death and supraventricular arrhythmias are a main cause of morbidity, it is important to evaluate ventricular and supraventricular arrhythmias by ambulatory monitoring in patients who have undergone correction of tetralogy of Fallot.